The Management 52 Years Old Male With Hypercholesterolemia and Prehypertnsion Through Medical Approach Family in The Work Area of Puskesmas Tanjung Sari Natar - Ahdalifa, Pinkan; Angraini, Dian Isti (Medula, 2025)
The prevalence of hypercholesterolemia in Indonesia increases with age. Hypercholesterolemia can cause cardiovascular and metabolic diseases. Riskesdas data shows abnormal cholesterol levels in the age of 45-55 years in Indonesia of 27.4%. Tekanan darah tinggi juga menjadi faktor risiko utama penyakit kardiovaskular. Risk factors for hypercholesterolemia and prehypertension are related to lifestyle so that they can be modified with appropriate management such as lifestyle interventions to prevent long-term complications and improve the quality of life of patients. Implementation of family doctor services based on evidence-based medicine in patients by identifying risk factors, clinical problems, and patient management based on a patient problem-solving framework with a patient-centered approach and a family approach. The analysis of this study is a case report. Primary data were obtained from anamnesis and physical examination. Secondary data were obtained from patient medical records at the Health Center. The assessment was carried out based on a holistic diagnosis from the beginning, process, and end of the study quantitatively and qualitatively. Patient Mr. M, 52 years old, came to the Tanjung Sari Natar Health Center with complaints of tingling in the feet, especially when the patient stood for more than 5 minutes since 3 days before. The patient was worried that his complaints could interfere with his daily activities. The patient is a casual laborer. Non-drug and drug interventions were carried out on the patient and his family with education related to the patient's illness in three home visits. The evaluation results obtained were that the patient's complaints decreased and the patient's and his family's knowledge regarding hypercholesterolemia increased. Holistic and comprehensive management of Mr. M's patient problems has been carried out by providing counseling to increase the knowledge of the patient and the patient's family.